Emergency Medicine in the #MeToo Era. (30th June 2019) - Marco, Catherine A.; Geiderman, Joel M.; Schears, Raquel M.; Derse, Arthur R.
Abstract: Sexual harassment is a serious threat to a safe and productive workplace. The emergency department (ED) environment poses unique threats, including stress, time constraints, working in close physical proximity, and frequent personal contacts with staff, colleagues, consultants, and difficult patients. Sexual harassment must be recognized and addressed in individual cases, in policy and in law, to protect staff members and patients. This article addresses the scope of the problem of sexual harassment known to date. It describes the ED environment and culture and why they may be conducive to harassment or abusive behavior. The authors examine relationships among staff, legal and regulatory issues, and strategies for prevention and remediation of inappropriate behavior. The article ends with a call for future research.